Identification of functional SNP associated with sperm quality in porcine ANXA5 that contributes to the growth of immature Sertoli cell - Han, Mingyang; Yao, Diwen; Song, Yuyang; Liu, Yuhang; Chen, Zhihua; Li, Jialian; Li, Fenge; Yang, Xiuqin; Dai, Lihe; Niu, Buyue (Frontiers in Veterinary Science, 2025)
AnnexinA5 (ANXA5) has been identified as a positional candidate gene for reproduction and fertility traits in boars, but its role in testicular tissue development, as well as genetic variations remain unclear. The aim of this study was to explore the effect of ANXA5 in the growth of swine Sertoli cells and identify its functional variations. Firstly, the expression of porcine ANXA5 in different tissues was detected by semi-quantitative RT-PCR and its effect on the proliferation of Sertoli cells was evaluated by CCK8, EdU, flow cytometry analyses and qRT-PCR. Then, putative causative variants were screened by integrating in silico analysis and DNA sequencing, and the subsequent association analysis was performed in Largewhite boars. Lastly, dual luciferase reporter assay was used to clarify the effect of specific SNP or ESR1 on ANXA5 transcription. The results showed that ANXA5 expressed in all the detected tissues, promoted proliferation of Sertoli cells by advancing cell cycle progression from the G1 to S phase and encouraging expression of PCNA. Putative causative variants, including two ns-SNPs within the coding region, and three closely linked SNPs in the promoter region were identified. Statistical analysis showed that the frequency of the T allele at g.-676 T > C, A allele at g.-674C > A, and T allele at g.-105G > T were each 0.75, the heterozygotes of Yorkshire boars had greater sperm motility as compared to TT, AA, and TT animals (p < 0.05). Luciferase reporter analysis suggested g.-105G > T and ESR1 modulated ANXA5 transcription. Taken together, this study demonstrated ANXA5 affected swine immature Sertoli cells growth and g.-105G > T was a candidate genetic marker for reproductive trait of boar.